Hydrological Response Assessment under Land Cover Change in The Krueng Layan Sub-Watershed Pidie Regency - Andri Renaldi, Teuku; Monalisa Yusri, Queen; Ariq Naufal, Muhammad (Universitas Iskandar Muda, 2026)
Land use change is one of the factors affecting watershed hydrological characteristics and flood discharge. This study aimed to analyze land-use changes between 2013 and 2023 and to evaluate their impact on flood discharge in the Krueng Layan Sub-watershed, Tangse District, Pidie Regency, Aceh Province. Land use maps were analyzed using QGIS, while design rainfall was estimated using the Normal, Log Normal, Gumbel, and Log Pearson Type III distributions. Flood discharge was then estimated using the Soil Conservation Service Synthetic Unit Hydrograph method. The results showed that primary forest, agricultural land, and Paddy fields decreased during the study period, whereas secondary forest, Settlement, and open land increased. Flood hydrograph analysis indicated that peak discharge under the 2023 land use condition was consistently higher than that of 2013 for all return periods. For the 100-year return period, peak discharge increased from 13.46 m³/s to 14.62 m³/s. These findings indicate that cumulative land-use changes between 2013 and 2023 altered the watershed's hydrological response and contributed to higher flood discharge. The results provide useful information for watershed management and flood mitigation planning.